2016
DOI: 10.2139/ssrn.2798253
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect of Place: Evidence from Japanese-American Internment

Abstract: Recent research has stressed the importance of long-run place effects on income and economic mobility, but the literature has struggled to isolate the causal impact of location. This paper provides new evidence on these effects using administrative data on over 100,000 Japanese-Americans who were interned during World War II. Internees were conditionally randomly assigned to camps in seven different states and held for several years. Restitution payments paid in the early 1990s to the universe of surviving int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…51 Shoag and Carollo (2016) show that place effects impacted the relative fortunes of internees. 52 This would not be the first instance in which a shock forcing individuals to move against their will leads them to re-optimize in a way that improves labor market outcomes; this has been recently shown in settings where a forced move is driven by an Icelandic volcano (Nakamura et al, 2019), Soviet annexation of parts of Finland (Sarvimäki et al, 2019), or Hurricane Katrina (Sacerdote, 2012;Deryugina et al, 2018).…”
Section: Mechanisms Migration and Occupational Changementioning
confidence: 99%
See 2 more Smart Citations
“…51 Shoag and Carollo (2016) show that place effects impacted the relative fortunes of internees. 52 This would not be the first instance in which a shock forcing individuals to move against their will leads them to re-optimize in a way that improves labor market outcomes; this has been recently shown in settings where a forced move is driven by an Icelandic volcano (Nakamura et al, 2019), Soviet annexation of parts of Finland (Sarvimäki et al, 2019), or Hurricane Katrina (Sacerdote, 2012;Deryugina et al, 2018).…”
Section: Mechanisms Migration and Occupational Changementioning
confidence: 99%
“…Nakamura et al, 2019), it is interesting to check whether former internees who moved did so to areas of the country that turned out to experience greater growth than the ones they left behind. Shoag and Carollo (2016) document how geography mattered in determining the relative prospects of different internees.…”
Section: Sample Stability and Endogenous Attritionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we study the 5 We also thank Bente Bondebjerg from Dansk Flygtningehjaelp, who helped run these programs and provided further details in personal communication. 6 Other notable papers in the exogenous placement literature are Aslund et al (2009), Shoag andCarollo (2020), Peters (2019), Chetty et al (2016), Beaman (2011), Edin et al (2003, Gould et al (2004), and Imberman et al (2012). 7 Counties are sub-units of the geographic units (commuting zones) we consider below.…”
Section: The Danish Refugee Dispersal Policymentioning
confidence: 99%
“…Workers receive some labor market benefits when they live close to their parents (Kaplan, 2012;Kramarz and Skans, 2014;Coate, Krolikowski and Zabek, 2019) and workers also appear to move closer to their birth places after job displacements (Huttunen, Møen and Salvanes, 2018). But young people can also earn more when they move away from their birth places (Shoag and Carollo, 2016;Nakamura, Sigurdsson and Steinsson, 2016), implying that many people have a strong preference to remain. Many recent papers have also found that migration is unusually slow given high returns (Bound and Holzer, 2000;Dao, Furceri and Loungani, 2017;Yagan, 2017;Chetty and Hendren, 2018).…”
Section: Introductionmentioning
confidence: 99%